Analysis of risk factors for surgical site infection after colorectal surgery: a cross-sectional study in the east of China pre-COVID-19 - Sun, Hui; Jiang, Hua; Jiang, Zhi-Wei; Fang, Ge; Dai, Zheng-Xiang; Wang, Zhiguo; Sun, Xiang; Wang, Wen (Frontiers in Public Health, 2023)
Background: The occurrence of surgical site infection (SSI) can prolong the postoperative hospital stay, increase the economic burden of patients, and even endanger their lives. The purpose of this study was to investigate the incidence, risk factors, and microbiology of SSI after colorectal surgery (CRS) and to provide a basis for the prevention and control of SSI. Methods: A single-center, prospective, cross-sectional study of adult patients undergoing CRS was conducted from 2010-2019. Univariate and multivariate logistic regression models were used to collect and analyze demographic information, hospital characteristics, and potential perioperative risk factors of SSI. Results: A total of 3302 eligible patients were included in this study, with 213 cases experiencing SSIs, resulting in an infection rate of 6.45%. Notably, the incidence of SSI decreased from 13.33% in 2010 to 3.56% in 2019 (Ptrend < 0.001). Escherichia coli accounted for the majority of isolated microorganisms (37.09%), with 49 strains exhibiting resistance to one or more antibiotics (35.25%).. Multivariate analysis showed that diabetes, anastomosis leakage, wound classification (contaminated/dirty), operation duration, blood loss greater than 200ml, and NNIS risk index score for 2 or 3 were independent risk factors. Conversely, laparoscopic approach, preoperative bowel preparation and preoperative albumin levels emerged as protective factors against SSI after CRS. Furthermore, compared to non-SSI patients, SSI patients had a significantly higher 30-day mortality rate following surgery (0.23% vs 2.35%, p<0.05). Conclusion: SSI after CRS was susceptible to many factors, and the pathogen of SSI was mainly Escherichia coli. In clinical practice, measures such as correcting preoperative hypoproteinemia, choosing laparoscopic surgery, preoperative bowel preparation and shortening the duration of surgery should be taken to reduce the incidence of SSI.